Agronomic performance of sacarino sorghum assessed in the Cáceres-Mato Grosso region (Research, Society and Development, 2022)
The sweet sorghum [Sorghum bicolor (L.) Moench, belongs to the Poaceae family, has succulent stalks with high contents of fermentable sugars. The search for alternatives for the Brazilian sugar-alcohol and energy sector, the cultivation of sweet sorghum presents itself to the market with advantages, aiming its use for energy purposes such as: fast cycle and fully mechanized culture. This research aims to evaluate the agronomic performance of different cultivars of sweet sorghum under environmental conditions in the region of Cáceres, in order to provide the sugar and alcohol industry with the best cultivar for ethanol production. The experiment was conducted in the 2019/20 harvest in the experimental area of the Laboratory of Genetic Resources & Biotechnology (LRG&B) at UNEMAT, in Cáceres. Twenty-five sweet sorghum genotypes, provided by EMBRAPA, were evaluated. The experiment was installed in a random block design, with three replications. The characteristics evaluated were flowering, height, green mass weight, dry mass weight, broth weight, average broth volume, total soluble solids and ton of brix per hectare. Submitted to analysis of variance and comparison of means by the Scott-Knott grouping of means test. The coefficients of variation presented for the characteristics ranged from 1.63 to 39.69%, in this sense, the coefficient of variation can be influenced by the edaphoclimatic conditions of the crop. The cultivars that most stood out obtaining better results for this region were CMSXS5035, CMSXS5036 and CMSXS5037 in average broth volume, broth weight, green mass weight, dry mass weight and obtained good results in a ton of Brix per hectare.